A Facile One-Pot Synthesis of Chromen-2-one Derivatives Fused with Five Membered Heterocycles - Tasqeeruddin, S.; S. Al-Arifi, Abdullah; Dubey, P.K. (Asian Journal of Chemistry, 2013)
A facile one-pot synthesis of 3-benzoxazol-2-yl-chromen-2-ones (4) by the condensation of chromen-2-one-3-carboxylates (1) with o-hydroxy aniline (3) is being reported in this paper. Alternatively 3-benzoxazol-2-yl-chromen-2-ones are prepared from chromen-2-one-3-carboxylic acids (2). The structures of all the products have been established by their spectral and analytical data.